Molecular Interaction Studies in Binary Liquid Mixtures from Ultrasonic Data - N. Santhi; PL. Sabarathinam; M. Emayavaramban C. Gopi; C. Manivannan (E-Journal of Chemistry)
Ultrasonic velocities and densities of the binary liquid mixtures of dimethy1 sulphoxide (DMSO) with phenol, o-cresol, m-cresol, p-cresol and p-chlorophenol at 318.15 K, over the entire composition range were measured. The theoretical values of ultrasonic velocity were evaluated using the Nomoto’s Relation (NR), Ideal Mixture Relation (IMR), Free Length Theory (FT) and Collision Factor Theory (FLT). The validity of these relations and theories was tested by comparing the computed sound velocities with experimental values. Further, the molecular interaction parameter (α) was computed by using the experimental and the theoretical ultrasonic velocity values. The variation of this parameter with composition of the mixtures has been discussed in terms of molecular interaction in these mixtures.